Guidance on Reading and Memorizing Short Letters for Children in Kliwed Village, Kertasemaya District, Indramayu Regency - Karsinih (Konsultan Jurnal Ilmiah Indonesia, 2024)
Jami' Al-Isti'la Mosque is a mosque located in Kliwed Village, Kertasemaya District, Indramayu Regency, which is used as a place to recite for children who want to learn Quran, however, there is a problem that is still a problem in terms of reading, namely the lack of applying the correct knowledge of tajweed. Children who recite only apply the pronunciation of huruh hijaiyah without applying the correct knowledge of tajweed. The purpose of this activity is to provide learning to children who recite so that their reading is in accordance with the science of tajweed. The method used in mentoring is to face-to-face teach ngaji to children who recite at the Jami' Al-Isti'la mosque. The result of dedication is an increase in the ability to read the Qur'an with tajweed.